Intercultural communication challenges and the coping strategies among fresh graduates in the Vuca Era - Melly Ridaryanthi; Anindita Susilo; Nevita Kristine (Penerbit Universiti Kebangsaan Malaysia, 2024)
Higher education has provided a set of curriculum to equip graduates with complete skill sets to enter the industry. Hard skills, as well as soft skills, are inseparable components for graduates to acquire. Industries today have rapidly changed due to the advancement of technology. Almost every aspect of life is going digital; therefore, graduates have to adapt to the simultaneous and continuous changes. In this situation, intercultural communication competence is one of the skills that will accommodate the fresh graduate to face and overcome challenges in the industry, especially in the VUCA era. All industrial players should adapt to the working cultures and adopt the advanced technological changes. This study explores the experience of fresh graduates in the industry regarding intercultural communication challenges and their coping strategies to overcome the situations. The phases of their adaptation towards the work environment will be addressed as well to understand the context better. Interviews were conducted to explore and understand their experience which eventually categorised to identify strategies that could accommodate the continuously changing situation. This study will contribute to the preparation of graduates to enter the workforce as the study found that there are three main challenges faced among fresh graduates regarding skill mismatch, lack of experience, and career adaptability. Furthermore, intercultural communication competence has contributed to their adaptation and coping strategies towards those challenges in their first job.